Assessment of femur and tibia subchondral parts mineral bone density in gonarthrosis - E M Zaitseva; A V Smirnov; L I Alexeeva (Научно-практическая ревматология)
Objective. To assess association between bone mineral density (BMD) of parts of femur and tibia gonarthrosis stage. Material and methods. 53 female with bilateral gonarthrosis aged 42 to 84 years with body mass index from 21,2 to 43 kg/m2 were included. Knee joints X-ray examination, densitometry of lumbar spine, femoral neck and condyles of femur and tibia were performed. Subchondral BMD assessment was done in 5 regions of knee. Results. Increase of gonarthrosis stage was accompanied by rise of subchondral tibia BMD values. Increase of medial femur condyles BMD was associated with knee joint space decrease, presence of subchondral osteosclerosis and marginal osteophytes so as knee varus deformity. Subchondral femur BMD values correlated only with the presence of marginal osteophytes.